Relative faecal abundance of extended-spectrum β-lactamase-producing Enterobacterales and its impact on infections among intensive care unit patients: a pilot study. (June 2021) - Pilmis, B.; Mizrahi, A.; Péan de Ponfilly, G.; Philippart, F.; Bruel, C.; Zahar, J.-R.; Le Monnier, A.
Summary: This pilot prospective study assessed the association between the faecal relative abundance of extended-spectrum β-lactamase-producing Enterobacterales (ESBL-PE) and the occurrence of ESBL-PE related infections. Twenty-four patients were included. The median ESBL relative abundance was 32.4%. The mean ESBL-PE relative abundance (ESBL-PE-RA) was more than five-fold higher in patients exposed during the last three months to antibiotics ( P  = 0.002). Furthermore, the mean ESBL relative abundance was more than two-fold higher in patients colonized with non- E. coli strains ( P  = 0.044). The mean ESBL-PE-RA was more than 10-fold higher for the concordant patients than for the discordant patients (59.1% vs 4.9%; P < 0.001).